Effectiveness of Ulinastatin in Combination with Amino Acid Solutions in Patients with Sepsis - Nurullaeva, Gulmira Amudullaevna; Atashov, Aybek Raimberganovich; Urinboev, Tolibjon Ganjaboy ugli (Central Asian Journal of Medical and Natural Science, 2025)
Sepsis remains one of the leading causes of mortality in intensive care units, particularly in obstetric pathology. Despite advances in modern treatment methods, mortality rates remain high due to the complex pathogenesis of sepsis. The systemic inflammatory response, characterized by excessive production of pro-inflammatory cytokines such as IL-6 and TNF-α, plays a central role in the development of multiple organ dysfunction. Ulinastatin, a protease inhibitor with pronounced anti-inflammatory and organ-protective properties, has shown promise in modulating the inflammatory cascade. At the same time, specialized amino acid solutions provide metabolic support, improve nitrogen balance, and restore immune function. The combined use of ulinastatin and amino acid solutions may represent a synergistic therapeutic strategy. This study evaluates the clinical efficacy of this combination in patients with sepsis based on cytokine dynamics, organ dysfunction (SOFA score), and mortality outcomes.